Archive-Based Multiobjective Evolutionary Algorithm for Large-Scale EV Charging Station Energy Management. (3rd September 2021) - Sheng, Wanxing; Duan, Qing; Wang, Haoqing; Sha, Guanglin; Ma, Chunyan
Abstract : With the increase in renewable energy, improving the utilization rate of renewable energy is of great practical significance. The microgrid has been proved effective in addressing this issue. As a flexible load, electric vehicles are connected to the grid on a large scale, which will have an impact on the grid. In order to solve this problem, this paper proposes a microgrid energy management model for electric vehicle charging stations, which takes into account the economics of microgrid operation and the stability of grid operation. Subsequently, this paper proposes an evolutionary multiobjective optimization algorithm to deal with constraints. Finally, this paper verifies the effectiveness of the proposed model and algorithm through experiments.